On the Role of Mast Cells and Their Proteases in the Severe COVID-19 - A. V. Budnevsky; S. N. Avdeev; E. S. Ovsyannikov; I. A. Savushkina; O. N. Choporov; V. V. Shishkina; A. V. Pertsev; I. M. Perveeva; N. G. Alekseeva (Архивъ внутренней медицины)
During the pandemic of the new coronavirus infection COVID-19 the question about the importance of mast cells and their proteases arose.   The aim of this study is to determine the role of mast cells and their proteases chymase and tryptase in the pathogenesis of severe COVID-19.   Materials and methods. The study included 55 patients: 29 male (52,7 %) and 26 female (47,3 %) aged 67 [62;71] years with severe COVID-19 and fatal outcome. An analysis of postmortem lung biopsies of patients with COVID-19 was carried out, determining the representation of mast cells, protease profile and degranulation activity. A correlation analysis was carried out between mast cell and clinical and laboratory parameters of patients.   Results. Increased number of mast cells and their degranulation activity were found in patients with chronic heart failure, obesity, chronic kidney disease, coronary heart disease and acute cerebrovascular accident. Degranulation of tryptase-positive mast cells are depleted as the duration of the disease increases: the content of single tryptase-positive mast cells (%) negatively correlates with the duration of the disease and hospitalization (p = 0,015, r = -0,327 and p = 0,006, r = -0,368, respectively), the content of tryptase-positive mast cells fragments (%)correlates with the duration of hospitalization (p = 0,007, r = 0,357). Correlations were established between the levels of non-conjugated bilirubin and alanine aminotransferase with the content of single tryptase-positive mast cells (per mm2) (r = 0,340, p < 0,05 and r = 0,307, p < 0,05, respectively), as well as single degranulated tryptase-positive mast cells (per mm2) (r = 0,369, p < 0,05 and r = 0,363, p < 0,01, respectively), and the level of conjugated bilirubin with the content of single tryptase-positive mast cells (%) (r = 0,415, p < 0,05). The blood calcium level correlates with the absolute total content of single tryptase-positive mast cells (p = 0,013, r = 0,457), as well as degranulated (p = 0,017, r = 0,441). A negative correlation was also found between potassium level and the relative content of single non-degranulated tryptase-positive mast cells (p = 0,014, r = -0,352). Correlations were found between the level of total bilirubin at the time of admission and over time with the content of single degranulated chymase-positive mast cells (per mm2) (p = 0,043, r = 0,277 and p = 0,027, r = 0,317, respectively). Urea level upon admission positively correlates with the absolute total content of single chymase-positive mast cells (p = 0,045, r = 0,277), as well as degranulated (p = 0,04, r = 0,283). The potassium level in the blood correlates with the total content of co-adjacent chymase-positive mast cells (p < 0,05, r = 0,388), as well as content of co-adjacent degranulated chymase-positive mast cells (p < 0,05, r = 0,388).   Conclusion. Significant correlations were noted between mast cells parameters and duration of the disease and hospitalization, the presence of comorbidities, unconjugated and conjugated bilirubin, ALT, urea, total protein, sodium, potassium and calcium blood levels. An increase in the number of mast cells and their degranulation activity has been found in patients with comorbidities: chronic heart failure, obesity, chronic kidney disease, ischemic heart disease and previous stroke. The revealed depletion of degranulation processes of tryptase-positive mast cells as the duration of the disease increases indicates their role in lung damage. We noted participation of mast cells and their proteases chymase and tryptase in the development of liver and kidney damage in patients with COVID-19, which confirms their importance in the severe course of the disease and may be considered in the future for the development of pathogenetic therapy.